Accessible search and the role of metadata. Issue 1 (19th March 2018) - Beyene, Wondwossen Mulualem; Godwin, Thomas
Abstract : Purpose: Some of the usability and accessibility problems of search interfaces emanate from poorly organized search results, where different types of metadata are employed. Metadata is important to make well-informed selection of resources. However, putting too much of it on search interfaces could be counterproductive. Therefore, studies suggest that metadata-related decisions need to be informed by user requirements. The purpose of this paper is to explore library metadata from usability and accessibility perspectives. It identifies search-related problems users with print disability face and explores how metadata-related decisions could be tailored to improve their experience in resource discovery and access. Design/methodology/approach: A questionnaire was posted online for two months. It targeted people with print disability who are using the audiobook app Lydhør. It was finally possible to gather responses from 113 respondents. Two open-ended questions dealing with search and metadata issues were selected for qualitative analysis. Findings: Most respondents mentioned the Lydhør's intolerance to spelling errors as a problem. Some suggested the use of faceted metadata, such as genres, for exploratory search to offset frustration caused by spelling errors. Most respondents indicated the importance of summaries to be shown among search results, implying their significance for lookup searches. There have been few demands related to accessibility metadata. Originality/value: This study could be a valuable input for inclusive/universal design of library search interfaces.